How smallholder farmers adapt to climate change: Stories from West Africa - Nana H (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Helene Nana is a female farmer from the Yatenga province in Burkina Faso. She describes in the video how she moved from famine to have more than enough income to get her children to school. This was accomplished through crop diversification and from growing vegetables to complement the rainy's season harvest. She has also installed a small pump, bought through a micro finance loan, that serves her with water from the nearby dam. Nowadays several other women in the area have a vegetable garden and the villagers are occupied even during the dry seasons.